THE EFFECT OF SOCIAL MEDIA MARKETING ON PURCHASE INTENTION DECISION PRODUCT by.U: THE MEDIATING ROLE OF BRAND IMAGE, BRAND AWARENESS AND BRAND EQUITTY - Rafsanjani, Ali Akbar; Rachawati, Indira; Trianasari, Nurvita (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
The by.U product is the first digital prepaid cellular service in Indonesia that provides an end-to-end digital experience for all telecommunications needs. by.U was developed specifically for the Gen Z segment in Indonesia, which at that time was projected to number around 44 million people. The company continues to market this product so that it becomes the choice of consumers, including by implementing several marketing methods which will be studied in this research. This research aims to determine the description of social media marketing activities, brand image, brand awareness and Brand Equity at by.U based on respondents' opinions. This study uses quantitative data collected based on filling out questionnaires carried out by 272 respondents who have used or are currently using by.U products, with the criteria that people who follow or have followed by.U social media have the desire to buy byU products in the future come. Sampling was carried out by purposive sampling. Data analysis was carried out using SEM techniques via the SmartPLS application. This study shows that social media marketing activities have a significant influence on brand awareness and brand image, which in turn contribute positively to brand equity and purchase intention. Apart from that, brand awareness and brand image are proven to play an important role in increasing brand equity and consumer purchasing interest in by.U products.